Donations, who are involved: a study on donations in virtual live presentations using QR Code in a COVID-19 pandemic context - Costa, Thiago Chiorino (2021)
Study objective: To know the importance of donations during the pandemic period with the aid of virtual live events and understanding what factors influence individuals to make donations during this crisis. Thus, we aim to verify how the involvement in virtual live streams, presentations, the attitude in helping others, and the use of new technology (QR Code), affect this new donation process.Method: We collected data from 291 individuals, and with validated scales, developed the data collection instrument. For the analysis of the model, we used the structural equation modeling (SEM) technique and Partial Least Squares (PLS).Main results: The analysis of the structural model confirmed that the attitude of helping others mediates the relationship between involvement with virtual live presentations and the intention to donate. However, the attitude towards using the QR Code was not significantly related to the intention to donate.Theoretical contributions: Our study contributes to the theories related to consumer behavior, particularly in situations related to engaging in fundraising actions for charity.Relevance / originality: The originality of our study is evident in the investigation of the behavioral intention of donation to charity in an atypical context (COVID-19 pandemic) through new tools and scenarios (use of QR Code).Management or social implications: Our study discusses the impact of technology on making donations possible and how event organizers can contribute to charities.